2016
DOI: 10.1002/ptr.5620
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phenolic Acids ofMacrotyloma uniflorum(Horse Gram) Protect the Rat Heart Against Isoproterenol-Induced Myocardial Infarction

Abstract: The present study investigates the cardioprotective activity of the Macrotyloma uniflorum seed extract (MUSE) and its phenolic acids (p-coumaric acid and ferulic acid) in isoproterenol (ISO)-induced myocardial infarction in rats. The previously mentioned phenolic acids were isolated and quantified from MUSE by HPLC. Pretreatment of gemfibrozil (reference standard), MUSE (250 and 500 mg/kg) and the phenolic acids for 30 days to rats treated with ISO (85 mg/kg) on the last 2 days resulted in a significant attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In our previous study, we found that angoroside C can be metabolized to ferulic acid in rats, which is one of the functional phenolic acids that commonly exist in a variety of plants, and multiple biological and pharmacological properties such as anti-oxidant ( Perezternero et al, 2017 ), anti-inflammatory ( Salazar-López et al, 2017 ), anti-obesity ( Salazar-López et al, 2017 ), and anti-depression ( Liu et al, 2017b ) have been reported for this compound. Most important of all, ferulic acid has been demonstrated to have protective effects against myocardial ischaemia ( Liu et al, 2016 ; Panda et al, 2016 ), which is usually considered to induce ventricular remodeling. Therefore, it is important and meaningful to pay more attention to the pharmacokinetic characteristics of ferulic acid in vivo after the oral administration of angoroside C during pharmacodynamic evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that angoroside C can be metabolized to ferulic acid in rats, which is one of the functional phenolic acids that commonly exist in a variety of plants, and multiple biological and pharmacological properties such as anti-oxidant ( Perezternero et al, 2017 ), anti-inflammatory ( Salazar-López et al, 2017 ), anti-obesity ( Salazar-López et al, 2017 ), and anti-depression ( Liu et al, 2017b ) have been reported for this compound. Most important of all, ferulic acid has been demonstrated to have protective effects against myocardial ischaemia ( Liu et al, 2016 ; Panda et al, 2016 ), which is usually considered to induce ventricular remodeling. Therefore, it is important and meaningful to pay more attention to the pharmacokinetic characteristics of ferulic acid in vivo after the oral administration of angoroside C during pharmacodynamic evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…17 The extracts of M. uniflorum also exhibited significant analgesic, anti-inflammatory, diuretic hepatoprotective and cardioprotective activities. [18][19][20] These activities may be mediated through the antioxidant properties of seeds of M. uniflorum.…”
Section: Discussionmentioning
confidence: 99%
“…Both coumaric acid and ferulic acid have been reported to attenuate pathological cardiac remodeling. In addition, studies suggest that ferulic acid inhibits HDAC activity [ 74 , 120 , 121 , 122 , 123 ]. Combined, these studies would suggest that hydroxycinnamic acids protect the heart, in part, through direct changes in gene expression.…”
Section: Phytochemicalsmentioning
confidence: 99%